TikTok Influence on Generation-Z Purchase Intention towards Offline F&B Businesses in Indonesia - Tarigan, Renalta; Aprianingsih, Atik (Journal of Business and Management, 2021)
Covid-19, the acceleration of technology and booming applications like TikTok opens up opportunities for businesses. It is important for them to understand the influential factors in TikTok so marketing strategies can be conducted as effectively and efficiently as possible. This research focuses on businesses in the Food & Beverages sector which is a large sector in Indonesia that is believed to be immune to the pandemic and is even predicted to develop rapidly along with technology advancement. This study adopted the Buyer Behavior theory by Howard and Sheth as the base theory. A 7-Point Likert Scale online questionnaire filled out by 199 respondents from Generation-Z who use TikTok everyday and have purchased culinary products that appear on TikTok at least once. The analysis was carried out using Structural Equation Modeling through the statistical application of SPSS and AMOS. This study found that Informational Based Content and E-WOM had a significant effect on Brand Attitude and Purchase Intention. Meanwhile, Recreational Based Content and Involvement with a Brand only have a significant effect on Brand Attitude. This study also found that Brand Attitude has proven significant to be a mediating variable.Keyword: TikTok; Purchase Intention; Generation-Z; Structural Equation Modeling; Food and Beverages Business